2016
DOI: 10.1177/0022034516653743
|View full text |Cite
|
Sign up to set email alerts
|

Painful Temporomandibular Disorder

Abstract: In 2006, the OPPERA project (Orofacial Pain: Prospective Evaluation and Risk Assessment) set out to identify risk factors for development of painful temporomandibular disorder (TMD). A decade later, this review summarizes its key findings. At 4 US study sites, OPPERA recruited and examined 3,258 community-based TMD-free adults assessing genetic and phenotypic measures of biological, psychosocial, clinical, and health status characteristics. During follow-up, 4% of participants per annum developed clinically ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
270
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(300 citation statements)
references
References 43 publications
12
270
3
15
Order By: Relevance
“…Indeed, in contrast to many other major diseases in which common immutable factors (gender, age, race) have substantial contributions, we note that for acute TMD the major predictor (3) thin solid arrows that indicate contributions from the stated factors into potential disease onset, transition or chronicity; (4) fat solid arrows that indicate the state shift from premorbid to acute, to transition state and to chronic state; and (5) the specific identification of disease-related person characteristics (DRPC)-particular aspects of the 'person' attached to each phase of the pain disorder, in order to emphasize that the disorder exists not alone but in the context of a person-state related to that disorder at that phase. This model builds on previously published work; see Slade et al, 2016) for summaries and results related to identified nodes in the Figure. In addition, the model extends into the post-onset period, thereby suggesting hypothesized patterns of interaction across time with moderating and mediating variables. Premorbid factors are comprised of: person-level variables of problems with stress and coping, psychological distress, general body tenderness, anxiety, impaired sleep, functional symptoms, other pain disorders, and pain sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, in contrast to many other major diseases in which common immutable factors (gender, age, race) have substantial contributions, we note that for acute TMD the major predictor (3) thin solid arrows that indicate contributions from the stated factors into potential disease onset, transition or chronicity; (4) fat solid arrows that indicate the state shift from premorbid to acute, to transition state and to chronic state; and (5) the specific identification of disease-related person characteristics (DRPC)-particular aspects of the 'person' attached to each phase of the pain disorder, in order to emphasize that the disorder exists not alone but in the context of a person-state related to that disorder at that phase. This model builds on previously published work; see Slade et al, 2016) for summaries and results related to identified nodes in the Figure. In addition, the model extends into the post-onset period, thereby suggesting hypothesized patterns of interaction across time with moderating and mediating variables. Premorbid factors are comprised of: person-level variables of problems with stress and coping, psychological distress, general body tenderness, anxiety, impaired sleep, functional symptoms, other pain disorders, and pain sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, TMD are often associated with, for example, mood disorders. Other risk factors are bruxism, certain genetic factors, migraine, tension-type headache, other chronic pain conditions, and a history of trauma, as described in the longitudinal OP-PERA study [71][72][73][74][75]. Whether an aberrant dental occlusion is a risk factor for TMD is still debated, although the existing evidence shows no clear-cut association between TMD symptoms or signs and malocclusion [76,77].…”
Section: Facial Pain As Encountered By the Stomatologist And Dentistmentioning
confidence: 99%
“…Temporomandibular disorders (TMD) are a cluster of conditions that cause pain and dysfunction in the temporomandibular joint, masticatory muscles, and surrounding structures, e.g., ligaments and connective tissues [1,2]. It causes high suffering to those affected in the community and is a widespread problem in clinical practice [2][3][4][5]. TMD affects 10-15% of the adult population and seems to be three times more frequent in women [1,2].…”
Section: Introductionmentioning
confidence: 99%